Régimen MYPE Tributario y su incidencia en la situación económica - financiera de la empresa E&C Ingenieros EIRL. Trujillo, año 2017. - Castañeda Chavez, Sarai Bethsabe (2019)
ABSTRACT This research was carried out in order to determine the impact of the MYPE Tax Regime on the economic and financial situation of the E&C engineers EIRL. Trujillo, year 2017. The type of study was descriptive, the design of a non-experimental study and the methodology of observational research, the accounting area was taken as a sample; the data was collected through the application of an interview and documentary analysis, the same ones that were ordered, classified and transcribed in auxiliary records using Microsoft Office Word 2010, as well as Microsoft Office Excel 2010 spreadsheets through simple and double-entry tables; From the data processed, it was verified that the income of the company in 2017 amounted to 2,177,344, which allowed for the use of the MYPE Tax Regime, the rate used for the determination of the Annual Income Tax in the fiscal year 2016 was 28% and for To determine the income tax in 2017, it was in accordance with progressive and cumulative rates that were applied to net income: up to 15 Tax Units 10%, more than 15 Tax Units 29.50%, which allowed to cancel a lower income tax compared to the general regime in 2016, thus obtaining greater profitability and liquidity, in this sense, it was concluded that the MYPE Tax Regime positively affects the economic-financial situation of the E&C engineers EIRL. Trujillo, year 2017.